2019
DOI: 10.20944/preprints201906.0003.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Induction of Apoptosis and Cell Cycle Arrest in two Human Cancer A549 and HT29 Cells Lines by Barhi Date Palm Kernels Extracts and Three Isolated Cytotoxic Compounds

Abstract: Background and objectives: The initiation of apoptotic death in cancer cells is the aim of many chemotherapeutic strategies. As many anticancer agents have been discovered in natural plant sources, the search for novel phytochemicals displaying anticancer activities continues at a tremendous rate. This study was conducted to evaluate the effect of extractable polyphenols (EPP); non-extractable polyphenols (NEPP); nobiletin (NOB); tectorigenin (TEC) and persicogenin (PERS) from Barhi date palm kernels (BDPK) ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
(24 reference statements)
1
5
0
Order By: Relevance
“…Our previous work [13] confirmed that the NEPP extracts of BDPK demonstrated selective cytotoxicity towards human lung (A549) and colon cancer (HT29) cell lines while being less cytotoxic against the normal cells. Such selective cytotoxic activity suggested that the "active substances interacted with special cancer-associated receptors or cancer cell special molecule, thus triggering some mechanisms that cause cancer cell death" [41].…”
Section: Evaluation Of Extraction Timesupporting
confidence: 61%
See 4 more Smart Citations
“…Our previous work [13] confirmed that the NEPP extracts of BDPK demonstrated selective cytotoxicity towards human lung (A549) and colon cancer (HT29) cell lines while being less cytotoxic against the normal cells. Such selective cytotoxic activity suggested that the "active substances interacted with special cancer-associated receptors or cancer cell special molecule, thus triggering some mechanisms that cause cancer cell death" [41].…”
Section: Evaluation Of Extraction Timesupporting
confidence: 61%
“…The extraction of polyphenols from plant materials is strongly influenced by many factors; extraction time, temperature and solvent-to-sample ratio among other factors [31,32]. Since the previous results [13] indicated that the EPP from BDPK were strong antioxidants and showed cytotoxic effects in selected human cancer cells, this research was carried out with the aim of optimising critical process parameters (extraction temperature, time and solvent/sample ratio) affecting the extraction of NEPP from BDPK using RSM in order to simultaneously maximise possible extraction of the TPC, TFC, TPAC with high DPPH• scavenging capacity and anticancer effects of NEPP extracts on A549 and HT29 human cancer cells.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations